THE EFFECT OF RELIABILITY AND EMPATHY ON PATIENT SATISFACTION AND ITS IMPLICATIONS ON PATIENT TRUST (Study at Melati Hospital, Sungai Penuh City, Jambi Province) - Maulana; Dr. Taufik Zulfikar, S.E., M.M; Dr. Ayu Laili Rahmiyati, S.KM., M.M; Dr. Taufan Nugroho, Sp.And., MMRS; Dr. Haddan Dongoran, S.E., M.Si; Assoc. Prof. Dr. VIP Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Service quality is an important factor in increasing patient satisfaction and building trust in healthcare institutions. This study aims to analyze the influence of reliability and empathy on patient satisfaction and their implications for patient trust at Melati Hospital in Sungai Penuh City, Jambi Province. The research method used is a quantitative approach with a survey method. The study sample consisted of 92 inpatient respondents selected using a probability sampling technique with the Slovin formula. Data were collected through questionnaires and analyzed using path analysis. The results showed that reliability and empathy have a positive and significant effect on patient satisfaction. Patient satisfaction was also proven to have a significant effect on patient trust. In addition, reliability and empathy have a direct effect on patient trust. The results of the Sobel test indicate that patient satisfaction is able to mediate the influence of reliability and empathy on patient trust. The research model shows a coefficient of determination value of 0.811, meaning that 81.1% of the variation in patient trust can be explained by the variables of reliability, empathy, and patient satisfaction. These findings confirm that improving service quality through the dimensions of reliability and empathy can increase satisfaction and strengthen patient trust in hospitals.